Diagnostic Utility of Pleural Fluid Cytology versus Cell Block Technique: A Comparative Study - Acharya, Subarna (Journal of Nepalgunj Medical College, 2023)
Introduction: Categorization between benign and malignant pleural effusions most often create diagnostic dilemma. Categorization often requires clinical findings and morphological evaluation. Diagnostic possibility is increased if cell blocks are performed in addition to conventional cytology smears. This will help the clinicians in both treating the patient and determining the outcome of the disease process. Aims: The aim of this study was to compare the smears cytology with cell blocks sections in pleural effusions. Methods: This hospital-based cross sectional analytical study was carried out in Department of Pathology in Nepalgunj Medical College, Nepalgunj for one year. Results: The four criteria scored for each technique were amount of background blood, yield of diagnostic cellular material, degree of cellular degeneration as well as cellular trauma and architectural preservation. More amount of diagnostic material present and appropriate retention of architecture was more in cell block sections compared with smears cytology; whereas cellular degeneration as well as cellular trauma and background blood was less appreciated in cell block sections which scored more than the smears cytology. Conclusion: Cell block method especially in clinically, radiologically and cytologically suspected malignant cases should be routinely processed for cell block method.